Three-dimensional cell culture conditions promoted the Mesenchymal-Amoeboid Transition in the Triple-Negative Breast Cancer cell line MDA-MB-231 - Rodríguez-Cruz, Daniela; Boquet-Pujadas, Aleix; López-Muñoz, Eunice; Rincón-Heredia, Ruth; Paredes-Díaz, Rodolfo; Flores-Fortis, Mauricio; Olivo-Marin, Jean-Christophe; Guillén, Nancy; Aguilar-Rojas, Arturo (Frontiers in Cell and Developmental Biology, 2024)
Breast cancer (BC) is the leading cause of death among women, primarily due to its potential for metastasis. As BC progresses, the extracellular matrix (ECM) produces more type-I collagen, resulting in increased stiffness. This alteration influences cellular behaviors such as migration, invasion, and metastasis. Specifically, cancer cells undergo changes in gene expression that initially promote an epithelial-to-mesenchymal transition (EMT) and subsequently, a transition from a mesenchymal to an amoeboid (MAT) migration mode. In this way, cancer cells can migrate more easily through the stiffer microenvironment. Despite their importance, understanding MATs remains challenging due to the difficulty of replicating in vitro the conditions for cell migration that are observed in vivo. To address this challenge, we developed a three-dimensional (3D) growth system that replicates the different matrix properties observed during the progression of a breast tumor. We used this model to study the migration and invasion of the Triple-Negative BC (TNBC) cell line MDA-MB-231, which is particularly subject to metastasis. Our results indicate that denser collagen matrices present a reduction in porosity, collagen fiber size, and collagen fiber orientation, which are associated with the transition of cells to a rounder morphology with bleb-like protrusions. We quantified how this transition is associated with a more persistent migration, an enhanced invasion capacity, and a reduced secretion of matrix metalloproteinases. Our findings suggest that the proposed 3D growth conditions (especially those with high collagen concentrations) mimic key features of MATs, providing a new platform to study the physiology of migratory transitions and their role in BC progression.